Transformation of Laves phases and its effect on the mechanical properties of TIG welded Mg-Al-Ca-Mn alloys. (1st September 2022) - Chai, Sensen; Zhong, Shiyu; Yang, Qingshan; Yu, Daliang; Dai, Qingwei; Zhang, Hehe; Yin, Limeng; Wang, Gang; Yao, Zongxiang
Highlights: The transformation of Laves phases in heat resistant Mg-Al-Ca-Mn alloys was clarified in details concerning the Ca/Al ratio and welding thermal cycle. Gradient microstructure evolution, dynamic dissolution and reprecipitation in the heat affected zone were characterized and demonstrated. Owing to the transformation of Laves phases, the mechanical properties of the joints were significantly enhanced. Hardness peak was reached in the heat affected zone due to the re-precipitation of Laves phases and Al8 Mn5 phases. Abstract: The effects of Al content and Ca/Al mass ratio on the microstructure and mechanical properties of tungsten inert gas (TIG) welded Mg-2Ca- x Al-0.5Mn ( x =0, 1, 5) alloy joints were studied in present work. Results showed that increasing Al content was effective in reducing the dendrite spacing at the fusion zone (FZ) edge. The Laves phases in the FZ and the heat-affected zone (HAZ) can be changed from Mg2 Ca to (Mg, Al)2 Ca with the decrease of Ca/Al ratio, and the (Mg, Al)2 Ca could be further transformed to Al2 Ca under welding thermal cycle. Furthermore, dynamic dissolution and precipitation of Laves phases and Al8 Mn5 phases occurred in the HAZ, resulting in a gradient microstructure and hardness peak in this area. The tensile properties of the joints were significantly improved with the increase of Al content, which was mainly due to the modification of Laves phases. Abstract : Image, graphical abstract